Performance of Banks in Pakistan based on determinants of Profitability - AQSA SIDDIQ; KHURSHEED IQBAL; SHAMS UR REHMAN (Journal of Business & Tourism, 2021)
The study aims to seek the internal factors that affect the profitability of banks in Pakistan from a period of 2009 to 2013 by using two proxies i.e. Return on Assets (ROA) and Return on Equity (ROE). The panel data of fifteen banks have been obtained from the financial statements of the banks. Therefore, Hausman test has verified that random effect model is most appropriate model for Return on Assets (ROA), conversely fixed effect model is prominent for Return on Equity (ROE) for the current study. The empirical results confirm that investment to total assets, leverage, Net Performing Loan (NPL) to gross advances, capital ratio and total deposits to total equity are the main determinants of profitability across both proxies (i.e. ROA and ROE). Leverage and capital ratio have significantly negative, however net performing loan to gross advance and total deposit to total equity have significantly positive influence on profitability of banks across both models. Moreover, NPL to gross advance is insignificant determinant of Return on Equity. The results are worthy for bankers and all stakeholders to make strategic decision for the competitiveness of banking sector in Pakistan.